2020
DOI: 10.1101/2020.03.25.20043331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Machine Learning Model Reveals Older Age and Delayed Hospitalization as Predictors of Mortality in Patients with COVID-19

Abstract: Objective: The recent pandemic of novel coronavirus disease 2019 is increasingly causing severe acute respiratory syndrome (SARS) and significant mortality. We aim here to identify the risk factors associated with mortality of coronavirus infected persons using a supervised machine learning approach.Research Design and Methods: Clinical data of 1085 cases of COVID-19 from 13 th January to 28 th February, 2020 was obtained from Kaggle, an online community of Data scientists. 430 cases were selected for the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…In some studies, older age was reported as a factor associated with mortality in SARS and MERS (25). The current study confirmed that old age was associated with mortality in patients with COVID-19, which is consistent with the findings of previous studies (22,24,26). In the univariate analysis, underlying diseases such as cardiovascular disease and hypertension were associated with mortality, as was reported similarly by Jordan (24).…”
Section: Discussionsupporting
confidence: 92%
“…In some studies, older age was reported as a factor associated with mortality in SARS and MERS (25). The current study confirmed that old age was associated with mortality in patients with COVID-19, which is consistent with the findings of previous studies (22,24,26). In the univariate analysis, underlying diseases such as cardiovascular disease and hypertension were associated with mortality, as was reported similarly by Jordan (24).…”
Section: Discussionsupporting
confidence: 92%
“…Several clinical predictive models have recently been proposed for COVID-19, for example, for predicting potential COVID-19 diagnoses using data from emergency care admission exams [ 60 ] and chest imaging data [ 61 - 66 ], for predicting COVID-19–related mortality from clinical risk factors [ 67 , 68 ], for predicting which patients will develop acute respiratory distress syndrome from patients’ clinical characteristics [ 69 ], for predicting critical illness in patients with COVID-19 [ 70 , 71 ], and for predicting progression risk in patients with COVID-19 pneumonia [ 72 ]. Siordia [ 73 ] presented a review of epidemiology and clinical features associated with COVID-19, and Wynants et al [ 74 ] performed a critical review that assessed limitations and risk of bias in diagnostic and prognostic models for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two other studies applied machine learning algorithms to predict mortality in patients with COVID-19, using patient data from Kaggle and China. 11,12 We propose that machine learning algorithms can be used to allocate priorities in receiving the RT-PCR tests in the case of a shortage, and also to help with critical care decisions while the RT-PCR results are being processed (which have been frequently taking more than a week in most places of Brazil). A promising area for future research will also be to analyze the combined performance of the new rapid tests and the machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%